Decentralization Elections in Jordan (2017): An Analytical Study - Al Sarhan, Atallah (Dirasat: Human and Social Sciences, 2020)
This study aims to analyze the results of the 2017 Decentralization elections (provincial councils), and to examine the contents of the Decentralization law number (49) for the year (2015). It also provides a digital analysis of the demographic and general characteristics of the members of the provincial councils such as gender, religion, age, qualification, profession; and the numbers of members of provincial councils, and the composition of provincial councils in general. The study focuses on the level of political participation at the general level of the governorates, which was low. The general participation percentage in the Kingdom reached (31.71%). While participation in the electoral process in the urban areas such as the large cities of Amman and Zarqa decreased to (17.56%), (20.06%), respectively, it increased in predominantly tribal towns such as Ajloun, Mafraq, and Karak, and the percentages were respectively (62.81%), (59.80%), (57.14%). This was due to certain economic, social, and political factors. The Decentralization law contributed to the increase in the representation of women (as they won )52( seats out of )380( seats, with a percentage of (13.68%)). The study refutes its hypothesis that "Decentralization elections enhance the level of political participation in the management of local affairs." The opposite has happened with low levels of participation because of many different variables as shown by the study.